Adaptation and delivery of a motivational interviewing-based counseling program for persons acutely infected with HIV in Malawi: Implementation and lessons learned. Issue 6 (June 2018) - Grodensky, Catherine A.; Golin, Carol E.; Pack, Allison P.; Pettifor, Audrey; Demers, Michele; Massa, Cecelia; Kamanga, Gift; McKenna, Kevin; Corneli, Amy
Highlights: Two evidence-based MI interventions were adapted for Malawians with acute HIV infection. Malawian counselors and clinicians contributed to intervention adaptation. Counselors and participants benefited from safer sex topics and goal-setting. Rating importance and confidence did not help participants explore barriers to behavior change. Abstract: Objective: Individuals diagnosed with acute HIV infection (AHI) are highly infectious and require immediate HIV prevention efforts to minimize their likelihood of transmitting HIV to others. We sought to explore the relevance of Motivational Interviewing (MI), an evidence-based counseling method, for Malawians with AHI. Methods: We designed a MI-based intervention called "Uphungu Wanga" to support risk reduction efforts immediately after AHI diagnosis. It was adapted from Options and SafeTalk interventions, and refined through formative research and input from Malawian team members and training participants. We conducted qualitative interviews with counselors and participants to explore the relevance of MI in this context. Results: Intervention adaptation required careful consideration of Malawian cultural context and the needs of people with AHI. Uphungu Wanga's content was relevant and key MI techniques of topic selection and goal setting were viewed positively by counselors and participants. However, rating levels of importance and confidence did not appear to help participants to explore behavior change as intended. Conclusion: Uphungu Wanga may have provided some added benefits beyond "brief education" standard of care counseling for Malawians with AHI. Practice implications: MI techniques of topic selection and goal setting may enhance prevention education and counseling for Malawians with AHI.